Legal Analysis of Judge's Determination on Marriage Dispensation Applications After the Issuance of the Supreme Court Regulation of the Republic of Indonesia Number 5 of 2019 - Duwirdja Haris; Akbar, Muhammad; B, Taufan; Suhri Hanafi (State Islamic University Datokarama Palu, 2024)
Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Trialing Applications for Marital Dispensation after it is enacted, clearly describes the procedures and conditions for applications, how to settle cases, and submitting legal remedies. The purpose of this study is: to analyze the law on judge decisions and to understand the judge's considerations in taking the dispensation of marriage after the birth of Perma Number 5 of 2019 in Determination Number 28/Pdt.P/2021/PA.Pso at the Poso Class II Religious Court. The method used is because it is a type of empirical legal research; it uses a qualitative approach because the problems relate to humans, which fundamentally depend on observations whose research design uses field research by conducting observations, interviews, and documentation to the parties at the research location. The results of this study indicate that the judge used the legal analysis in case Number 28/Pdt.P/2021/PA.Pso uses maqashid al-Syari'ah and statutory regulations that are interconnected and sorted according to degree and year of publication. Regarding the judge's consideration in deciding case Number 28/Pdt.P/2021/PA. Pso used psychological considerations, and there was no compelling reason that what the Petitioner wanted so that his request was granted turned out to be rejected because of these considerations. The implication is that judges at the Poso Class II Religious Court are encouraged to attend training/guidance as Juvenile Judges so that they are more progressive in demonstrating their capacity to understand Islamic Law by matching it with statutory regulations in analyzing cases of the dispensation of marriage. Parents are advised to play an important role in providing supervision and attention to children in order to avoid things that deviate due to promiscuity and the government's role in socializing the age limit for marriage.